2010
DOI: 10.1509/jmkg.74.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Customer Reactions to Service Separation

Abstract: Recent research suggests that inseparability is not a universal distinguishing characteristic of services and that the consumption of many services is or can be separated from their production. This research defines service separation as customers' absence from service production, which denotes the spatial separation between service production and consumption. In a series of qualitative and quantitative studies across different services, the authors examine customer reactions to service separation. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(135 citation statements)
references
References 45 publications
9
124
1
1
Order By: Relevance
“…This is important because of the focus on the customer's perspective to date in the literature, with little known about the providers' experience. For example, recent research by Keh and Pang (2010) demonstrated that customer reactions to service separation are generally favourable. Although service separation increased customer's perceptions of 'access convenience and benefit convenience' it also increased 'performance risk and psychological risk' (Keh and Pang, 2010, p.55).…”
Section: Why Service Separation?mentioning
confidence: 99%
See 4 more Smart Citations
“…This is important because of the focus on the customer's perspective to date in the literature, with little known about the providers' experience. For example, recent research by Keh and Pang (2010) demonstrated that customer reactions to service separation are generally favourable. Although service separation increased customer's perceptions of 'access convenience and benefit convenience' it also increased 'performance risk and psychological risk' (Keh and Pang, 2010, p.55).…”
Section: Why Service Separation?mentioning
confidence: 99%
“…Services' marketing is defined in terms of its origins and distinction from physical products based on the four characteristics of intangibility, heterogeneity, inseparability and perishability (Lovelock and Gummesson, 2004). Next, the infusion of technology (Bitner, 2001a;2001b) is reviewed in response to the breakdown of the inseparability assumption and the rise of separated service delivery (Keh and Pang, 2010;Paluch and Blut, 2013). Several types of technology infused service are reviewed, reflecting the shift from high touch low tech, to high tech, low touch service delivery (Schumann et al, 2012).…”
Section: Structure Of the Thesismentioning
confidence: 99%
See 3 more Smart Citations